2016
DOI: 10.1016/j.jid.2015.12.038
|View full text |Cite
|
Sign up to set email alerts
|

ABCB5-Targeted Chemoresistance Reversal Inhibits Merkel Cell Carcinoma Growth

Abstract: Merkel cell carcinoma (MCC) is a highly aggressive neuroendocrine skin cancer with profound but poorly understood resistance to chemotherapy, which poses a significant barrier to clinical MCC treatment. Here we show that ATP–binding cassette member B5 (ABCB5) confers resistance to standard-of-care MCC chemotherapeutic agents and provide proof-of-principle that ABCB5 blockade can inhibit human MCC tumor growth through sensitization to drug-induced cell cytotoxicity. ABCB5 expression was detected in both establi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
20
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 19 publications
(20 citation statements)
references
References 27 publications
0
20
0
Order By: Relevance
“…In the current study, based on previously established functions in diverse malignancies (18,21,(24)(25)(26)(27)(28), we examined the potential of ABCB5 as a novel therapeutic target in GBM. Our results revealed ABCB5 expression in primary human GBM tumors and three established GBM cell lines.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In the current study, based on previously established functions in diverse malignancies (18,21,(24)(25)(26)(27)(28), we examined the potential of ABCB5 as a novel therapeutic target in GBM. Our results revealed ABCB5 expression in primary human GBM tumors and three established GBM cell lines.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, ABCB5 was found to be highly upregulated in the ALDH bright CSC subpopulation in the human U-87 MG GBM cell line (23). Moreover, ABCB5 has been established as a key mediator of tumor growth, aggressiveness, and multidrug resistance (MDR) in malignant melanoma, colorectal cancer, hepatocellular, oral squamous and Merkel cell carcinomas, and ocular surface squamous neoplasia (18,21,(24)(25)(26)(27)(28). Here we hypothesized that, similar to its role in other cancers, ABCB5 might contribute to malignant growth and therapy resistance of GBM.…”
Section: Introductionmentioning
confidence: 99%
“…2b), differently from AC. Since ABCB5, a transporter of several drugs present in tumor IC, 16,17,22 was significantly upregulated in six out of six IC compared to AC (Fig. 1e), we investigated its role in MPM IC chemoresistance.…”
Section: Abcb5 Determines Chemoresistance In Mpm Icmentioning
confidence: 99%
“…As previously said, ABCB5 is a marker of cancer stem cells and is implicated in the tumorigenesis and tumor growth of several neoplasms, such as cutaneous melanoma, breast cancer and hepatocellular carcinoma [9][10][11][12][13][14][15][16]. Particularly, Wang et al [17] found that in vitro ABCB5-negative melanoma cell sub-population displayed a reduction in cell migration and invasion compared to the ABCB5-positive one; this finding was also confirmed at the transwell assays: lentivirus-mediated knockdown of ABCB5 in two different melanoma cell cultures induced a decline of cell migration and invasion.…”
Section: Discussionmentioning
confidence: 96%
“…ATP-binding cassette sub-family B member 5 (ABCB5) is a human transmembrane P-glycoprotein that plays an active role in transmembrane transport of several substances including chemotherapeutic drugs; therefore, it is physiologically involved in the development of chemoresistance of cancer cells [9][10][11]. An overexpression of ABCB5 has been found in tumor stem cells, of which it is therefore a full-fledged marker of several malignancies such as hepatocellular carcinoma, breast cancer, cutaneous melanoma and Merkel cell carcinoma [12][13][14]. Furthermore, ABCB5 has been shown to be correlated with tumor growth and invasion [15,16].…”
Section: Introductionmentioning
confidence: 99%